Limits to tourism growth in LDCs - Klaus M. F. Edelmann (Intereconomics, 1975)
The following is an attempt by the author to analyse tourist relations between industrial nations and LDCs and to describe predictable conflict situations which may arise if these relations are subjected to excessive physical and psychological strains or if the international division of labour in the field of “holiday production” becomes unbalanced.
Keywords: 330; Tourism